The Effect of RGEC on Financial Distress in Rural Banks – Conventional in The Central Kalimantan Region - Hendrianto, Didik (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study aims to analyze the effect of the ratio in the assessment of the health level of banks based on RGEC (Risk Profile, Good Corporate Govermance, Earnings, Capital) on the possibility of financial distress in Conventional Rural Banks in the Central Kalimantan Province region in 2019 - 2023, The population in this study were all Conventional BPRs operating in Central Kalimantan, with the sample used being the entire population. Data analysis using the Multiple Regression Analysis method, the results showed that: The NPL (Non Performing Loan) ratio has a significant negative effect on BPR financial distress so that the lower the NPL, the less likely the BPR will experience Financial Distress. The implementation of GCG has a significant negative effect on Financial distress, ROA has a significant negative effect on Financial destress, the higher the profitability of BPR reflected in ROA, the less likely it is to experience Financial Destress. CAR ratio has a significant negative effect on financial distress, because the higher the capital adequacy of BPR, the less likely it is to experience financial distress. The Loan Deposit Ratio has a Significant Positive effect on financial distress, because the higher the LDR, the more likely it is that the BPR will experience Financial Distress. Overall, the results of this study indicate that the ratio in the RGEC-based bank health assessment has a significant influence on the possibility of financial distress in Conventional Rural Banks in the Central Kalimantan Province region.